Effect of Sr substitution in La-Ca-Mn-O compound on structural and electrical properties - Wan Jusoh, Wan Nur Wathiq; Lim, Kean Pah; Awang Kechik, Mohd. Mustafa; Abdul Halim, Shaari; Ng, Siau Wei (Trans Tech Publications, 2016)
Polycrystalline manganites compound of La0.67A0.33MnO3 (A= Sr, Ca) has prepared by conventional solid state reaction method. In this work, an effort has been made to study the influences of substitution with different alkaline earth in La-site. The structural of La0.67A0.33MnO3 was studied by X-ray diffraction patterns (XRD), XRD spectrums of La0.67Ca0.33MnO3 (LCMO) showed in orthorhombic structure (space group Pbnm) while La0.67Sr0.33MnO3 (LSMO) was in hexagonal structure (R-2c). The LCMO and LSMO bulks were investigated magnetically in view to understanding the ferromagnetic-paramagnetic (FM-PM) behaviors using vibrating sample magnetometer (VSM) at room temperature. LSMO bulk sample exhibited ferromagnetic with high in magnetization while LCMO bulk was in paramagnetic behaviors. The Curie temperature and metal-insulator transition temperature (Tp) were measured using AC Susceptibility (ACS) at temperature range 78 K- 300 K and four-point probe technique. The Tc for LCMO was 260 K, the curves coincide at temperatures above 240 K and become zero around the Curie critical temperature, where the FM-PM transition occurs and Tp for LCMO was reported around 250 K. Meanwhile, the Tc and Tp for LSMO were above 300 K. The difference in grain sizes of the microstructure images of LCMO and LSMO are might be due to the substitution of variance alkaline earth ions that differs in grain growth were observed using scanning electron microscopy (SEM). By replacing Sr2+ in La-Ca-MnO, the crystal structure transform from orthorhombic to hexagonal with highly symmetrical, thus the MnO6 octahedral are less distortion and the local spins are relatively more aligned. Therefore, electron hopping interaction at sub-orbital (3d:eg) increase, resulting the Tc and Tp are shifted to higher values.